Intellectual Capital and Good Corporate Governance Determinants of Financial Performance - Herman Wijaya; Denny Kurnia; Kodriyah Kodriyah (Journal of Applied Business, Taxation and Economics Research, 2021)
The purpose of this study was to examine the effect of intellectual capital and good corporate governance on company performance. The population in this study were companies listed in the Jakarta Islamic Index during the 2016 – 2019 period. The sampling technique in this study used a purposive sampling technique. This causality research method was analyzed using multiple regression. The data collection method used is the secondary data documentation method, and tested using Partial Least Square (PLS-SEM). The result of this research is that there is an influence between Intellectual Capital on financial performance. The results of corporate governance proxied by the Board of Directors have a significant effect, but the Board of Commissioners and the Audit Committee have no effect on the Company's Financial Performance.